CLIMATE-ADAPTIVE SILVICULTURAL STRATEGIES FOR INDONESIAN TROPICAL FORESTS IN THE ERA OF CLIMATE CRISIS - Yahya Touray; Mariama Bah; Lamin Fofana (Yayasan Adra Karima Hubbi, 2026)
In the face of the escalating climate crisis, Indonesian tropical forests, one of the most biodiverse ecosystems in the world, are experiencing profound challenges. Climate change poses a significant threat to forest resilience, affecting biodiversity, water cycles, and carbon sequestration capacities. This research explores climate-adaptive silvicultural strategies aimed at enhancing the resilience of these ecosystems to climate-induced stresses. The study investigates the role of forest management practices, including species selection, planting techniques, and conservation methods, in promoting sustainable forest development. The research adopts a mixed-methods approach, combining field observations, climate modeling, and stakeholder interviews to assess current silvicultural practices and their effectiveness in climate adaptation. Data collected from diverse forest sites across Indonesia were analyzed to identify patterns of forest health, growth rates, and biodiversity preservation. Results indicate that adaptive silvicultural techniques, such as the use of native species, agroforestry systems, and selective logging practices, significantly enhance forest resilience. Furthermore, these strategies contribute to improved carbon sequestration, biodiversity conservation, and soil stability. This study concludes that climate-adaptive silviculture is crucial for mitigating the impacts of climate change on Indonesian tropical forests. Implementing these strategies will foster sustainable forest management, ensuring long-term ecological balance and ecosystem services.